2009
DOI: 10.1111/j.1474-9726.2009.00474.x
|View full text |Cite
|
Sign up to set email alerts
|

Centenarians – a useful model for healthy aging? A 29‐year follow‐up of hospitalizations among 40 000 Danes born in 1905

Abstract: SummaryCentenarians surpass the current human life expectancy with about 20-25 years. However, whether centenarians represent healthy aging still remains an open question. Previous studies have been hampered by a number of methodological shortcomings such as a cross-sectional design and lack of an appropriate control group. In a longitudinal population-based cohort, it was examined whether the centenarian phenotype may be a useful model for healthy aging. The study was based on a com- For example, at age 71-74… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
76
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 37 publications
(34 reference statements)
13
76
0
3
Order By: Relevance
“…Drei Viertel der dänischen Hundertjäh-rigen wurden in diesem Zeitraum wegen Pneumonie, Herzinfarkt, Schlaganfall, bösartigen Neubildungen und/oder Brü-chen im Hüftbereich behandelt. Trotz dieses hohen Ausmaßes an Morbidität kön-nen Hundertjährige als Modell gesunden Alterns angesehen werden: Im Vergleich zu den Mitgliedern ihrer Geburtskohorte (1905, Dänemark), die kein so hohes Alter erreichten, wiesen sie in jüngeren Jahren weniger und kürzere Krankenhausaufenthalte auf [18].…”
Section: Gesundheit Und Krankheit Im Hohen Und Höchsten Alterunclassified
“…Drei Viertel der dänischen Hundertjäh-rigen wurden in diesem Zeitraum wegen Pneumonie, Herzinfarkt, Schlaganfall, bösartigen Neubildungen und/oder Brü-chen im Hüftbereich behandelt. Trotz dieses hohen Ausmaßes an Morbidität kön-nen Hundertjährige als Modell gesunden Alterns angesehen werden: Im Vergleich zu den Mitgliedern ihrer Geburtskohorte (1905, Dänemark), die kein so hohes Alter erreichten, wiesen sie in jüngeren Jahren weniger und kürzere Krankenhausaufenthalte auf [18].…”
Section: Gesundheit Und Krankheit Im Hohen Und Höchsten Alterunclassified
“…There is also increasing evidence to support the existence of various factors (historically known as phosphatonins) that directly control the renal excretion of phosphorus, and elucidation of their precise role in the regulation of phosphorus metabolism is an area of active research [20,29,30] . These hormones and novel factors act on the primary target organs, bone, kidney, parathyroid glands and intestine to regulate systemic mineral metabolism ( table 1 ).…”
Section: Normal Phosphate Homeostasis and Alterations In Ckdmentioning
confidence: 99%
“…Studies have shown that increased serum FGF-23 and PTH, and decreased calcitriol levels precede the onset of clinical hyperphosphatemia during CKD progression ( fig. 1 ) [29,30] . In this regard, phosphaturic hormones are able to maintain normal levels of serum phosphate during the early stages of kidney disease [31][32][33] .…”
Section: Normal Phosphate Homeostasis and Alterations In Ckdmentioning
confidence: 99%
“…It has been shown that many centenarians have been healthy or well functioning throughout most of their lives; thus, centenarians represent a useful model for delayed aging [22]. Contemporary populations are subjected to rapid population aging; so identifying the pathways to healthy longevity are of particular importance.…”
Section: Introductionmentioning
confidence: 99%